The Effectiveness of Using Plotagon Story Media to Improve Listening Skills for Non-Arabic Speakers - M. Baihaqi; Muflihah; Ramadhani, Tasya Fajar (Journal of Arabic Language Studies and Teaching, 2023)
Digital learning has many benefits and importance in today’s information technology era. With digital learning, students can set the time and place of study according to their needs and preferences. This research has a problem formulation: how to use the Plotagon story in listening skill learning in Islamic Yunior High School 2 Surabaya, and how effective the use of the Plotagon story is in improving students’ listening competence. The population of this study was all grade 7 students, totaling 278 students, while the sample was 32 students studying in grade 7F. This quantitative research collects data through tests, namely prates and posters, and then ends with a t-test analysis. The results significantly increased after students followed digital learning with Plotagon stories. This problem is expected to be developed in other learning domains, such as speaking, reading, and writing competencies.